Pengaruh Usia Terhadap Kedisiplinan dan Produktivitas Pada Dinas Pertanian dan Ketahanan Pangan Kabupaten Karawang - Rahma Nurjaya; Syifa Pramudita (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Given the current situation regarding the influence of age on the performance and discipline of employees in government agencies, it indicates a significant weakness in the human resources field, particularly in the department, affecting the system and implementation of work programs. The objective of this internship is to assess the improvement of discipline and its impact on job productivity from the perspective of age at the Department of Agriculture and Food Security (DISTAN) in Karawang. This study was conducted using a qualitative descriptive implementation method with the aim of creating a systematic, factual, and accurate overview based on the facts on the ground. The results of the analysis in this research indicate that each variable, namely compensation, work discipline, and motivation, partially have significant positive and negative effects on employee productivity in government agencies, especially at the Department of Agriculture and Food Security. Based on the intern's research findings during the internship at the Department of Agriculture and Food Security in Karawang, age significantly contributes to poor discipline and work productivity. As employees approach retirement or have been working for a long time, they tend to neglect their duties and even exhibit absenteeism. Employees also demonstrate a lack of competence in following instructions. In addition to the challenges faced by employees, there are also challenges with each farmer group showing a lack of enthusiasm in extension activities, thereby hindering the progress of extension activities.